Dimerization and nuclear entry of mPER proteins in mammalian cells - Yagita, Kazuhiro (Cold Spring Harbor Laboratory Press, 2000)
Nuclear entry of circadian oscillatory gene products is a key step for the generation of a 24-hr cycle of the biological clock. We have examined nuclear import of clock proteins of the mammalian period gene family and the effect of serum shock, which induces a synchronous clock in cultured cells. Previously, mCRY1 and mCRY2 have been found to complex with PER proteins leading to nuclear import. Here we report that nuclear translocation of mPER1 and mPER2 (1) involves physical interactions with mPER3, (2) is accelerated by serum treatment, and (3) still occurs in mCry1/mCry2 double-deficient cells lacking a functional biological clock. Moreover, nuclear localization of endogenous mPER1 was observed in cultured mCry1/mCry2 double-deficient cells as well as in the liver and the suprachiasmatic nuclei (SCN) of mCry1/mCry2 double-mutant mice. This indicates that nuclear translocation of at least mPER1 also can occur under physiological conditions (i.e., in the intact mouse) in the absence of any CRY protein. The mPER3 amino acid sequence predicts the presence of a cytoplasmic localization domain (CLD) and a nuclear localization signal (NLS). Deletion analysis suggests that the interplay of the CLD and NLS proposed to regulate nuclear entry of PER in Drosophila is conserved in mammals, but with the novel twist that mPER3 can act as the dimerizing partner.